2019
DOI: 10.3390/sports7110237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Competitive Soccer Matches on Landing Biomechanics in Female Division I Soccer Players

Abstract: Fatigue has been proposed to increase the risk of knee injury. This study tracked countermovement jump, knee isometric strength, and kinetics and kinematics in 8 female soccer players (experimental group) during an anticipated sidestep maneuver before and after two matches played over a 43-h period. Time points were: Before and after match 1 (T0 and T1), 12 h after the first match (T2), and immediately after the second match (T3). A control group participated only in practice sessions. Isometric knee extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…As expected, the incidence rate during international matches (8.8 injuries per 1000 hours of exposure) was higher than during national matches (5.7 injuries per 1000 hours of exposure). Similar to that which has been found for male football players, the higher density of matches played, the mental stress and anxiety generated in the players, and the fact that international competitions are usually played during summer periods (at the end of a long season where accumulated fatigue may play a part) may be contributing factors for this difference [123,124].…”
Section: National Leagues Versus International Tournamentssupporting
confidence: 56%
“…As expected, the incidence rate during international matches (8.8 injuries per 1000 hours of exposure) was higher than during national matches (5.7 injuries per 1000 hours of exposure). Similar to that which has been found for male football players, the higher density of matches played, the mental stress and anxiety generated in the players, and the fact that international competitions are usually played during summer periods (at the end of a long season where accumulated fatigue may play a part) may be contributing factors for this difference [123,124].…”
Section: National Leagues Versus International Tournamentssupporting
confidence: 56%
“…The CMJ showed a pattern of increasing successively over the games. The increase in values is contrary to previously published literature in different sports [5,50,51]. This finding could be explained by a couple of reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…During official field hockey competitions, teams often play two consecutive games in less than twenty-four hours. This imposes high physical demands on an athlete, limiting physical performance in subsequent matches due to an insufficient recovery [5]. In other intermittent team sports such as soccer, research has shown that the demands of a single match can induce muscle damage and post-match fatigue that can last up to seventy-two hours [6].…”
Section: Introductionmentioning
confidence: 99%
“…sprinting, sportspecific movements and strength), biochemical markers in the blood (e.g. creatine kinase) and muscle soreness are all altered following competition [27][28][29]. This would seem to suggest that even for well-trained players, the demands of the game exceed those associated with training and that this stress results in a temporal disruption that limits relevant aspects of physiological function [30].…”
Section: Physical Demands Of Female Soccermentioning
confidence: 99%